Antibiotic residuals removal via novel fabricated hydrogel from 2-hydroxyethyl methacrylate and sodium methacrylate - Nahit Aktaş; Sinan Akgöl; Urmat Zholdoshbek Uulu (MANAS: Journal of Engineering)
In this study, poly(2-hydroxyethyl-sodium methacrylate) (p(HEMA-SMA)) hydrogels were synthesized as a novel adsorbent to remove antibiotic residues from environmental samples. [p(HEMA-SMA)] co-polymers were synthesized by the free radical photopolymerization method. Synthesized hydrogels were characterized by different methods such as Fourier-transform infrared spectroscopy (FTIR), elemental and scanning electron microscope (SEM), and surface area calculations. The average size surface area of the synthesized hydrogels were 1.515 µm. Penicillin G (Pen. G) was used as the sample antibiotic for the adsorption process. The absorption of the drugs was studied under different environmental conditions. Medium pH, temperature, and hydrogel concentration were varied to achieve the highest absorption. The specific adsorption value (Qmax) of p(HEMA-SMA) copolymers was found 303.03mg/g for Penicillin G at the 0,35 mg/mL of initial Pen. G concentration. In conclusion, we suggest a novel microstructure, selective, low-cost adsorption polymeric material for the removal of Pen. G as the template antibiotic.